Association between sleep status and lower urinary tract symptoms among men aged 40 or older in Zhengzhou - Zheng, Caifang; Ge, Yongchao; Chen, Xiaorui; Shao, Weihao; Wang, Gaili; Zhang, Bowen; Zhang, Weidong (Sleep and biological rhythms, 2022)
A cross-sectional study based on the community was conducted to explore the association between sleep status and LUTS among middle and old-aged men. Male residents in Zhengzhou aged 40 or older were recruited. Participants received the Pittsburgh Sleep Quality Index questionnaire and the International Prostate Symptom Score questionnaire to evaluate sleep status and the severity of lower urinary tract symptoms (LUTS), respectively. Logistic regression analyses and linear regression analyses were performed to evaluate the relationship between sleep quality and sleep duration and LUTS. A total of 5785 participants were enrolled. Multivariable analyses showed a positive relationship between sleep quality and LUTS ( β 0.716, 95% CI 0.647–0.784), and poor sleepers were significantly associated with moderate or severe LUTS (OR 2.486, 95% CI 2.095–2.950). U-shaped dose–response relationship revealed that sleeping less than 5.8 h/day and more than 7.9 h/day was related to moderate or severe LUTS and more than 7.9 h/day of sleep duration was associated with poor voiding and storage symptoms ( P for nonlinearity < 0.001). Similar relationship was observed between sleep status and nocturia. It showed a significantly positive relationship between sleep quality and LUTS. U-shaped dose–response relationships between sleep duration and LUTS were observed.